Nanoferritas de níquel multifuncionais: produção, propriedades e aplicações - Silva, Maitê Medeiros de Santana e (2022)
Spinels are magnetic semiconductor ceramics where the cationic distribution is given by the equation ( 1− 2+ 3+)[ 2+ 1− 3+ ] 2−4. Due to the variable atomic arrangement, determined by the type of cation present in the structure and the method of obtaining it, ferrites are multifunctional materials. The application of these materials in electrochemistry has been growing over the years and the possibility of using ferrites as electrodes, either for charge storage devices or in water splitting reactions, brings great opportunities for nanotechnology researchers. In this work we present the synthesis of nickel ferrite nanoparticles (NiFe2O4) by the combined EDTA-Citrate complexation method. We studied the influence of reaction pH (3, 5, 7 and 9) on powder properties and the influence of temperature on phase formation when the reaction pH was set at 7. Structural, morphological, optical, magnetic and electrochemical properties were evaluated. The results confirmed the obtaining of single-phase NiFe2O4 powders at all pH studied (3, 5, 7 and 9) with nanoscale particle size (15-93 nm). The morphology of the powders was affected by the reaction pH and exhibited rounded shapes, undefined shapes and triangles. UV-vis analysis reveals an inversely proportional relationship between crystal size and band gap. The isothermal hysteresis at 5 K and 300 K showed ferrimagnetic behavior for all samples obtained. The samples obtained without pH 3 and 9 were tested in an electrochemical cell in alkaline solution and it was found that for the purpose of use in energy storage devices the material was classified as battery-like electrodes. The improved electrochemical behavior of the NF9 sample (Qs = 65 C g-1 in 3 A g-1) was attributed to an increase in faradaic reactions driven by the porosity difference on the surface of the sample agglomerates and the boundary limits of the grains responsible for lower resistance to charge transfer. The NiFe2O4 powders, obtained at pH 7 at 400, 500 and 600 °C, were studied in alkaline solution as electrodes in oxygen evolution reactions reaching an overpotential of 326 mV vs. RHE to generate a current density of 10 mA cm-2 for samples calcined at 400 °C. The improved electrochemical behavior compared to literature data was attributed to the microstructural characteristics that affect the charge and mass transport processes and to the reduced particle size. Thus, the materials obtained are presented as magnetic semiconductors and can be applied in devices that require soft ferrimagnetic materials, as well as electrodes in storage devices or in OER reactions.